Vibration Characteristics of Quartz Crystal and Analysis of System Error in Fiber Optic Voltage Sensor - Yang, Hanrui; Guo, Yichang; Xu, Shibo; Xia, Linlin; Hong, Wei; Dong, Chunjun; Jiao, Shengxi (Frontiers in Physics, 2020)
The additional deformation of the quartz crystal under the vibration stress disturbance greatly affects the measurement accuracy of the fiber optic voltage sensor. In this paper, the influence of different vibration directions on quartz crystal deformation is analyzed by the finite element method based on the analysis and derivation of the system error mathematical model of the quasi-reciprocal reflected fiber optic voltage sensor. Furthermore, the effect of additional quartz crystal deformation on the output precision of the system is calculated. The results show that the vibration stress along the axial direction mainly causes the quartz crystal to deform in height, and the vibration stress along the radial direction mainly causes the quartz crystal to deform the circumference. Among them, the deformation of the crystal radial circumference is the main reason to influence the system output accuracy. In addition, the size and deformation parameters of the quartz crystal are related to the output error of the sensor system. This paper provides the parameter optimization and design guidance for improving the anti-mechanical vibration performance of the sensor head of fiber optic voltage sensor and provides a theoretical basis for the suppression method of the system error.